DO PERSONALITIES AND MOTIVATION AFFECT JOB PERFORMANCE? AN EVIDENCE FROM A RURAL BANK IN CENTRAL JAVA - Kurniawan Aji Prabowo; Praptini Yulianti (LPPM STIE Muhammadiah Bandung, 2022)
Good employee performance is the main thing for the company. Poor performance will cause the company to suffer losses, or it can even experience bankruptcy and liquidation. Until now, many rural banks in Indonesia are experiencing liquidation, so it is necessary to find a solution to improve the performance of rural bank employees in Indonesia so that liquidation can be avoided. This research aims to examine whether the big five personalities of employees and employee motivation can affect job performance. Data were collected from 50 employees of a rural bank X, in Central Java. Multiple regression analysis was used to analyze the data. The findings of this study are that the big five personality does not have a significant effect, while employee motivation has a significant effect. However, simultaneously these two variables can affect job performance.